Investigation of Entomopathogenic fungi of Soil Source in Plantation Cultivation Areas of North Kalimantan - Abdul Rahim; Syamsia (Postgraduate, University of Mataram, 2025)
Exploration and investigation in various locations are essential for identifying biological agent fungi that can be developed for pest control. This study determined identifying and comparing potential entomopathogenic fungi from different plantation areas. Soil samples were collected from oil palm (Sebuku), cocoa (Sebatik), and coffee (Malinau) plantations. We used T. mollitor insects to isolate and select the entomopathogenic fungi. We compared the mortality rates of insects exposed to each fungal isolate against a control group during the selection process. t-tests and descriptive analysis were utilized to evaluate the data. This study identified fifteen different fungal isolates. Most of these isolates were obtained from coffee plantations or areas in Malinau. However, only four isolates showed potential as entomopathogens. Furthermore, isolate ST16-3, when diluted to a concentration of 10-1, exhibited higher virulence than the other isolates. The virulence is reached 50.5%. The findings of this study suggested that plantations areas may potentially source of fungi entomopathogens.